Rhetorical style the uses of language in persuasion - Fahnestock, Jeanne 1945- (New York Oxford University Press, 2011)
A comprehensive guide to the language of argument, Rhetorical Style offers a renewed appreciation of the persuasive power of the English language.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Persuasion (Rhetoric); English language -- Rhetoric; English language -- Style